Neurologic disorders associated with weight lifting and bodybuilding - Busche, K. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
Weight lifting and other forms of strength training are becoming more common because of an increased awareness of the need to maintain individual physical fitness. Emergency room data indicate that injuries caused by weight training have become more universal over time, likely because of increased participation rates. Neurologic injuries can result from weight lifting and related practices. Although predominantly peripheral nervous system injuries have been described, central nervous system disease may also occur. This article illustrates the types of neurologic disorders associated with weight lifting.